Cervical Ripening Balloon in Combination with Methotrexate and Potassium Chloride for the Treatment of a 13-week Cervical Ectopic Pregnancy - Alina Tvina; Emily Smith; Meredith Cruz (Case Reports in Obstetrics and Gynecology)
Background. Cervical pregnancy, an uncommon type of ectopic pregnancy, can lead to devastating consequences if not diagnosed and treated early. Despite this, there are no specific guidelines on how to treat such pregnancies especially in advanced gestational ages (GAs). Case. This is a 35-year-old patient who presented to our hospital at 13 weeks GA after failing systemic multidose methotrexate therapy for a cervical ectopic pregnancy. Given desire to preserve fertility, a minimally invasive conservative approach was taken involving potassium chloride (KCl) and methotrexate injections into the gestational sac, followed by immediate Cook intracervical double balloon placement under direct ultrasound visualization, with removal of the balloon after 72 hours, and ultimately resolution of the pregnancy 12 weeks after the removal. Conclusion. Advanced first trimester cervical ectopic pregnancy after failure of methotrexate therapy was managed successfully with minimally invasive KCl and methotrexate injections in combination with cervical ripening balloon.